2021
DOI: 10.3390/nu13114070
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Protects H9c2 Rat Cardiomyoblasts from Doxorubicin-Induced Cardiotoxicity: Role of Caveolin-1 Upregulation and Enhanced Autophagic Response

Abstract: Doxorubicin (Doxo) is a widely used antineoplastic drug which often induces cardiomyopathy, leading to congestive heart failure through the intramyocardial production of reactive oxygen species (ROS). Icariin (Ica) is a flavonoid isolated from Epimedii Herba (Berberidaceae). Some reports on the pharmacological activity of Ica explained its antioxidant and cardioprotective effects. The aim of our study was to assess the protective activities of Ica against Doxo-detrimental effects on rat heart-tissue derived em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
1
10
0
Order By: Relevance
“…Our study confirmed that ICA could enhance DEX-induced podocyte autophagy and reduce the dose of hormone drugs. Similarly, in studies in which rat cardiomyocytes fight doxorubicin-induced cardiotoxicity, ICA has been shown to promote the lipidation rate of autophagy markers beclin-1 and LC3 and restore the physiological activation levels of protective autophagy [30]. This suggests that our study is consistent with the study of Scicchitano et al [30], which lays the foundation for the mechanism by which ICA treats nephrotic syndrome and other diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirmed that ICA could enhance DEX-induced podocyte autophagy and reduce the dose of hormone drugs. Similarly, in studies in which rat cardiomyocytes fight doxorubicin-induced cardiotoxicity, ICA has been shown to promote the lipidation rate of autophagy markers beclin-1 and LC3 and restore the physiological activation levels of protective autophagy [30]. This suggests that our study is consistent with the study of Scicchitano et al [30], which lays the foundation for the mechanism by which ICA treats nephrotic syndrome and other diseases.…”
Section: Discussionsupporting
confidence: 90%
“…For the detection of intracellular ROS, H9c2 cells (100,000 per well) were seeded on coverslips in 6-well plates and exposed to PA and PSELT, alone or in co-treatment for 24 h. At the end of the experimental protocol, H9c2 cardiomyocytes were incubated with 10 μmol/L CM-H 2 DCFDA at 37 °C for 30 min in the dark, and then the cells were carefully rinsed with DPBS and visualized under a fluorescence microscope (Olympus; 20× objective) [ 28 , 29 ]. For measuring the production of total ROS by flow cytometry, H9c2 cells were treated as above, collected, washed with DPBS, and stained with H2DCFDA.…”
Section: Methodsmentioning
confidence: 99%
“…However, the gastrointestinal concentration of EGCG especially in the jejunum was significantly increased after nanoparticle administration which is considered a major site for flavonoid absorption. 101 Icariin is another flavonoid known to exhibit cardio protection against ischemic heart disease, 102 cardiotoxicity, 103 and atherosclerosis 104 but limited by its poor pharmacokinetics. 105 Icariin was formulated as a nanodrug incorporated into monomethyl ether PEG (mPEG).…”
Section: Polyphenol Enclosed Nanocarriers In Cardiovascular Therapymentioning
confidence: 99%